PENGARUH PUPUK KOMPOS DAN FREKUENSI PEMBERIAN MOL BONGGOL PISANG TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS STROBERI (Fragaria sp.) - Nadhifa Hasna Fauziyah; Susilo Budiyanto; Adriani Darmawati Sudarman (BUANA SAINS, 2020)
The aim of the study was to know the influence of the rice straw compost doses as fertilizer and the frequence microorganism local of banana weevil on the growth and yield of the strawberry. The experimental design of this research was Completely Randomize Design (CRD) factorial with three factors of rice straw compost doses (15, 20, 25 tons/ha) and three factors of frequence microorganism local of banana weevil (1 time, 3 times, and 5 times) with 3 replications. The parameter observed were bulk density of soil, porosity of soil, organic ingredients of soil, number of leaves, number of fruit, and weight of fruit. Data obtained was processed by analysis of variance and if there is an effect of yield treatment continued with Duncan multiple range test. The result showed that there are interaction between two treatment on bulk density and soil porosity. The compost doses and frequence microorganism local of banana weevil had significan effect on soil characteristic (bulk density, porosity, and organic ingredients of soil), improvement of best soil characteristic happen on compost doses 20 tons/ha and frequency microorganism local of banana weevil 2 times. Treatment of compost doses application 25 tons/ha will improve the parameters of number of leaves and number of fruit, while the best weight of fruit happen on compost doses 20 tons/ha with frequency microorganism local of banana weevil 1 time.